Gray Scale Edge Detection using Interval-Valued Fuzzy Relations - Bouchet, Agustina (2015)
Gray scale edge detection can be modeled using Fuzzy Sets and, in particular, Interval-Valued Fuzzy Sets. This work is focused on studying the performance of several Interval-Valued Fuzzy Sets construction methods for detecting edges in a gray scale image. These construction methods are based on considering information related to the neighborhood of each point. Thus, several construction methods are proposed and tested, showing the approach performing better.